2024
DOI: 10.3233/ch-229105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Covid-19 disease on hemostasis dynamics during extracorporeal membrane oxygenation (ECMO)1

Abstract: INTRODUCTION: COVID-19 causes a considerable degradation of pulmonary function to the point of an acute respiratory distress syndrome (ARDS). Over the course of the disease the gas exchange capability of the lung can get impaired to such an extent that extracorporeal membrane oxygenation (ECMO) is needed as a life-saving intervention. In patients COVID-19 as well as ECMO may cause severe coagulopathies which manifest themselves in micro and macro thrombosis. Previous studies established D-dimers as a marker fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Kurihara et al noted that while there were no significant differences in mortality, patients infected with COVID-19 and receiving ECMO had a greater rate of thrombotic and bleeding complications than non-COVID-19 ECMO patients [ 12 , 17 ]. Additionally, Zheng et al reported more severe pneumonia and cardiovascular complications in COVID-19-infected patients with underlying cardiovascular disease [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kurihara et al noted that while there were no significant differences in mortality, patients infected with COVID-19 and receiving ECMO had a greater rate of thrombotic and bleeding complications than non-COVID-19 ECMO patients [ 12 , 17 ]. Additionally, Zheng et al reported more severe pneumonia and cardiovascular complications in COVID-19-infected patients with underlying cardiovascular disease [ 18 ].…”
Section: Discussionmentioning
confidence: 99%